Agronomic response of cocoa mucilago (Theobroma cacao L.) in maize culture (Zea mays L.) (2019)
The production of drained mucilage of beans of Theobroma cacao, T. grandiflorumand T. bicolorin wooden box was compared and then its possible use as biofertilizer was evaluated. T. cacaoshowed the highest production of drained mucilage (4.5 ml mucilage kg-1grain h-1) with contents of 11.18 mg P L.-1, 0.2% K and 0.08% N. Subsequently the growth of two varieties of Zea mays(ICA V-305 and Calilla) using drained mucilage of T. cacaowas characterized. The field experiment had five treatments (fertisun, control (without fertilizer), 5% mucilage, 10% mucilage and 15% mucilage) under a completely random design in divided plots. The agronomic response variables evaluated were: Absolute Growth Rate (AGR) and Relative Growth Rate (RGR). In the evaluation of AGR in the two varieties of Z. maysstudied, it was observed that the Calilla variety showed greater growth in less time when applied 5% mucilage with respect to the variety ICA V-305, for which it was considered the best treatment to use as biofertilizer. Considering the existence of weeds in the study site, which were only removed in the samplings at 13 and 21 days after seedling not clear tendency was observed in the RGR values for the two varieties of Z. maysevaluated.